2015
DOI: 10.1016/j.egja.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intrathecal dexmedetomidine in prevention of shivering in patients undergoing transurethral prostatectomy: A randomized controlled trial

Abstract: Background: Shivering is a frequent complication following spinal anesthesia (SA). It is more common in transurethral resection of the prostate (TURP) that may be due to absorption of large amount of irrigating fluids. We aimed to investigate the role of intrathecal dexmedetomidine in attenuation and prevention of shivering in patients undergoing TURP under SA. Methods: In a randomized, controlled trial, eighty patients were scheduled for elective TURP under SA. Patients were randomly allocated into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 27 publications
1
52
1
Order By: Relevance
“…With regard to shivering, the results of Moawad and Elawdy’s13 study are in agreement with the current study. The lower incidence of shivering compared with our study may relate to the higher dose of dexmedetomidine (10 μg versus 5 μg).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to shivering, the results of Moawad and Elawdy’s13 study are in agreement with the current study. The lower incidence of shivering compared with our study may relate to the higher dose of dexmedetomidine (10 μg versus 5 μg).…”
Section: Discussionsupporting
confidence: 92%
“…The secondary outcomes were the incidence of hypothermia, sedation, the use of meperidine to control shivering and complications. Results: Group C had significantly higher proportions of patients who developed shivering (21), developed grade IV shivering (20) and required meperidine (21) to treat shivering than group M (8,5,5) and group D (5,3,6) , which were comparable to each other. The time between block administration and meperidine administration was similar among the three groups.…”
Section: Introductionmentioning
confidence: 78%
“…Dexmedetomidine is a highly selective alpha-2-adrenoreceptor agonist with potent effects on the central nervous system, decreasing the sympathetic tone (5). It has been effectively used intravenously for the treatment (6-10) and prevention (11)(12)(13)(14) of shivering following SA without any major adverse effects in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects were reported in 15 studies, comprising neurological complications [24, 25, 28, 30], respiratory depression [22, 2426, 2830, 38, 44, 45], bradycardia [22–30, 36, 38, 44, 45], hypotension [22–27, 29, 30, 36, 38, 44, 45], nausea/vomiting [22–30, 36–39, 44, 45]. None of the studies reported mortality and major cardiovascular complications, such as non-fatal myocardial infarction, stroke, or cardiac arrest.…”
Section: Resultsmentioning
confidence: 99%
“…Dexmedetomidine, a highly lipophilic anesthetic [47], demonstrates almost 8- 10times higher affinity to α2-ARs than clonidine [48]. When administered as a neuraxial adjuvant, dexmedetomidine can quickly bind to dorsal horn of the spinal cord α2-ARs, subsequently to inhibit the spontaneous firing rate of neurons [49] and sympathetic tone [29]. However, mechanisms of hypothermia and shivering may differ in parturients.…”
Section: Discussionmentioning
confidence: 99%